The propagation of transient waves in two-dimensional square lattices. (January 2022) - Aleksandrova, Nadezhda I.
Highlights: Wave equations describing the plane motion of a 2D square lattice are splitted. Asymptotic solutions are obtained describing the propagation of antiplane and plane perturbations under a local step load. Numerical examples are given to demonstrate the accuracy of asymptotic solutions. For problems of mechanics of discrete-periodic media, a method is proposed for asymptotic inversion of the Fourier and Laplace transforms. Abstract: The aim of this article is to study the attenuation of transient low-frequency waves in 2D lattices in both plane and antiplane problems. The main idea of this article is that analytical solutions to problems of mechanics of discrete periodic media can be obtained by a method of asymptotic inversion of the Laplace and Fourier transforms in the vicinity of the quasi-front of infinitely long waves; moreover, in this method it is possible to take into account the contribution of short waves. Using this method, we obtain asymptotics of perturbations in lattices in plane and antiplane formulations under a local transient load. Besides, we show that equations describing 2D plane motion of a square lattice can be represented in the form of two linearly independent wave equations, each of which contains one unknown function only. By analogy with the theory of elasticity, one equation describes the propagation of shear waves in the lattice, while the other equation describes the propagation of longitudinal waves. As a result, it is shown that, in a homogeneous infinite lattice, a load can be specified in such a manner that either predominantly longitudinal or predominantly shear waves are formed. The problems under study are also solved by a finite difference method. The qualitative and quantitative correspondence of asymptotic and numerical solutions is shown.